A construção do cuidado em um programa de atendimento domiciliar ao acamado do município de Porto Alegre, RS - Freitas, Ivani Bueno de Almeida (Universidade do Vale do Rio dos Sinos, 2007)
In Brazil it is necessary to include elderly-patients care in the Basic Health Unit programs and to insert home care in the list of health care modalities. This article identifies features from a Home-care Program for Bedridden Patients" (PADA) situated within a Basic Health Unit in the most elderly-populated area in Porto Alegre, RS. To describe and to analyze PADA activities, in the years of 2005 and 2006, observing the program as a care pointer. Study of PADA case, whose analysis comprises a qualitative and a quantitative part (demographic data, main morbidities, growth of user's numbers in 2005 and 2006). The discussion was driven by qualitative observations given by home visits, nursing group(?), field diary and institutional documents. The PADA includes 35 users in 2005 and 31 bedridden patients in 2006. On both terms, most users was comprised of women, older than 80 years, with a 4 or 5 incapability degree. In 2006, there was a statistically significant increase of elderly patients inserted in the program (p=0,03). The cardiovascular diseases, Alzheimer/Dementia and cerebrovascular accident were the most common diseases. The lethality rate was 48% in 2005 and 41% in 2006 (p+0,17) indicating possible PADA influence.PADA has been considered a elder care pointer, from concepts such as the pointing condition. The quantitative evaluation of the program suggests attendance impact, shown in the reduction of the mortality rate, even though the number of elders, with ages from 80 years or older and bearing severe incapacity, has increased. The PADA creates new ways to nurture bedridden patients, caretakers elderly women mostly- and the health team itself, by utilizing the principles of taking care of self, in order to help others. It is hoped that the study collaborates with the reflection of the social-doers about new technologies for the care and the promotion of the Health Information System for home-care.
Keywords: Saúde coletiva; Idosos; Cuidados Médicos; ACCNPQ::Ciências da Saúde::Saúde Coletiva